2016
DOI: 10.1016/j.bodyim.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

“No fat friend of mine”: Young children's responses to overweight and disability

Abstract: Two studies investigated 4-to 6-year-old children's weight bias. In Study 1, 126 children read illustrated books where a main character ('Alfie') was healthy weight, in a wheelchair, or overweight. In Study 2, 150 children read the same stories where the character was female ('Alfina'), or stories where her friends were fat. Children rated 'Alfie'/'Alfina' and a comparison character on nine attributes/behaviours, and chose one that best represented each attribute. Fat and wheelchair 'Alfie'/'Alfina' were rated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 33 publications
6
27
0
2
Order By: Relevance
“…Three broad areas of investigation illustrate how informed children are by the age of 5. First, the negative stereotyping of fat body shapes or characters is apparent , with friendship preferences especially influenced . In these experiments, some very young children reflect back the weight bias that is prominent in society.…”
Section: Introductionmentioning
confidence: 94%
“…Three broad areas of investigation illustrate how informed children are by the age of 5. First, the negative stereotyping of fat body shapes or characters is apparent , with friendship preferences especially influenced . In these experiments, some very young children reflect back the weight bias that is prominent in society.…”
Section: Introductionmentioning
confidence: 94%
“…By age 5, parents of children with obesity are more likely to report peer relationship problems in their girls and boys than parents of healthy weight children [24•]. Five-year olds themselves reject story characters drawn as fat as people they would choose to be friends with [25•]. Rejection may be a very small step from perceived victimisation.…”
Section: Conceptualising Self-esteemmentioning
confidence: 99%
“…Conversely, other researchers found that boys as young as 4 years of age and as old as emerging adulthood were more likely to hold antifat attitudes than were girls (Damiano et al, ; O'Brien, Hunter, Halberstadt, & Anderson, ). Still others found no gender differences in weight‐based biases (Harrison et al, ). Given these mixed findings, this study will examine gender difference but will not make explicit predictions about gender differences in weight prejudice.…”
Section: Introductionmentioning
confidence: 95%
“…Non‐overweight children, adolescents, and young adults often attribute more negative traits to heavier peers such as “lazy”, “slow”, “gross”, “sad”, and “unattractive” compared to thin and normal‐weight peers (Brochu & Morrison, ; Greenleaf, Starks, Gomez, Chambliss, & Martin, ). Even young children (6 years and under) can demonstrate these negative attitudes toward overweight peers (Harrison, Rowlinson, & Hill, ; Margulies, Floyd, & Hojnoski, ; Puhl et al, ; Sagone & De Caroli, ). These weight‐based stereotypes can then lead to the dislike of overweight peers (Crandall, ; Crandall & Eshleman, ), which in turn can lead to weight‐based victimization such as name‐calling, physical aggression, and social exclusion (Puhl et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation